The state goes home: local hyper-vigilance of children and the global retreat from social reproduction - Katz, Cindi (Social justice, 2001)
The growing child protection industry has built its business foundation on an all-pervasive culture of fear, whilst hiding what its mission really is—the remaking of the home as a fortress through the sale of surveillance technologies to protect it from intrusion. These are totally inappropriate technocratic solutions for wide-ranging social problems and constitute another reaction to the poisonous and elusive rhetoric that has become one of the key stocks in trade of the neoliberal state.